2020
DOI: 10.5194/gmd-13-707-2020
|View full text |Cite
|
Sign up to set email alerts
|

TRAPPIST-1 Habitable Atmosphere Intercomparison (THAI): motivations and protocol version 1.0

Abstract: Upcoming telescopes such as the James Webb Space Telescope (JWST), the European Extremely Large Telescope (E-ELT), the Thirty Meter Telescope (TMT) or the Giant Magellan Telescope (GMT) may soon be able to characterize, through transmission, emission or reflection spectroscopy, the atmospheres of rocky exoplanets orbiting nearby M dwarfs. One of the most promising candidates is the late M dwarf system TRAPPIST-1 which has seven known transiting planets for which Transit Timing Variation (TTV) measurements sugg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(104 citation statements)
references
References 38 publications
3
101
0
Order By: Relevance
“…In this section, we do not consider stellar contamination and only discuss potential detections of atmospheric features of the TRAPPIST-1 planets. Here, we limit our discussion to include only the cases of TRAPPIST-1b, c, e and g because (a) b and c have the smallest periods -that is to say the most transits and therefore the greatest precision on measurements, (b) planet e is arguably the most promising candidate for habitability, for the reasons given in Wolf (2017Wolf ( , 2018, Turbet et al (2018) and Fauchez et al (2019a), and (c) planet g was the most observed with HST/WFC3 (Wakeford et al 2018).…”
Section: Transmission Spectra Of the Planetsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, we do not consider stellar contamination and only discuss potential detections of atmospheric features of the TRAPPIST-1 planets. Here, we limit our discussion to include only the cases of TRAPPIST-1b, c, e and g because (a) b and c have the smallest periods -that is to say the most transits and therefore the greatest precision on measurements, (b) planet e is arguably the most promising candidate for habitability, for the reasons given in Wolf (2017Wolf ( , 2018, Turbet et al (2018) and Fauchez et al (2019a), and (c) planet g was the most observed with HST/WFC3 (Wakeford et al 2018).…”
Section: Transmission Spectra Of the Planetsmentioning
confidence: 99%
“…(22)) is satisfied. We chose planets b and e because e is the planet that is the most likely to harbor liquid water on its surface (Wolf 2017(Wolf , 2018Turbet et al 2018;Fauchez et al 2019a) and b is the closest to the host star. We note that a planet could lie in the abiogenesis zone while not being in the classical habitable zone (Rimmer et al 2018), yet, by choosing to study planet e we maximize the similarities with Earth.…”
Section: Flaresmentioning
confidence: 99%
See 1 more Smart Citation
“…Note presently underway is the TRAPPIST-1 Habitable Atmosphere Intercomparison (THAI) project (Fauchez et al. 2020b ), where multiple 3-D GCMs will be compared for habitable iterations of TRAPPIST-1e. This is illustrated in Fig.…”
Section: Constraints From Numerical Modellingmentioning
confidence: 99%
“…The figure was taken from Fauchez et al. ( 2020b ) Planet h is further out where the classical CO 2 runaway collapse is supposed to take place. To reach temperate conditions, in addition to a very thick CO 2 atmosphere, the planet would need to retain enough volcanic gases such as CH 4 or H 2 in order to block CO 2 infrared windows and prevent the collapse of the atmosphere (Pierrehumbert and Gaidos 2011 ; Wordsworth et al.…”
Section: Constraints From Numerical Modellingmentioning
confidence: 99%